A Clinical Masquerader: Squamous Cell Carcinoma of the Eyelid Previously Diagnosed as an Eye Bump - Virk, Sanjeet Kaur; Fisher, April J.; Fisher, Brian D.; Rodriguez, Alexis (Canadian Journal of Optometry, 2019)
Malignant eyelid tumors are often difficult to diagnose at early stage growth, and can be clinically challenging. Due to the high prevalence of periocular skin cancers, clinicians must be very attentive in their assessment of skin lesions amongst their patients. This case report highlights an early non-healing eyelid lesion transforming into squamous cell carcinoma. An 83-year-old male with no history of malignancy presented with a non-healing and rapidly growing lesion of the left lower eyelid. He first noticed this lesion one-month prior and was treated with oral antibiotics without improvement by his primary care provider. Our slit lamp examination of the left eyelid revealed a large ulcerated mass with white mucoid discharge draining from the center of the lesion. After an oculoplastics referral, the patient was diagnosed with squamous cell carcinoma confirmed by biopsy. Computed tomography(CT) showed no metastasis or invasion to deep layer tissue. The management decision in this case required exenteration of the left eye socket followed by radiation therapy. This case illustrates the clinical course and invasive nature of periocular squamous cell carcinoma. It can present in a variety of different appearances, but are mostly painless, hyperkeratotic lesions that progressively change and ulcerate. An extensive history and careful clinical examination are vital in order to detect malignancy in a timely manner.